DETERMINAN PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) PADA BANK UMUM SYARIAH - Oktafiana; Yulian, Tri Nurindahyanti; Kristanto, Eri (JURNAL EKONOMI, 2024)
The purpose of this research is to examine the relationship between analyze the Effect of Cost Efficiency, Leverage, Institutional Ownership, and ProfitSharing Ratio on Disclosure of Islamic Social Reporting (ISR) in Islamic Commercial Banks Registered at OJK in 2018 – 2022. The sample in this study amounted to 51 data from 12 Islamic Commercial Banks which presented financial reports regarding variables related to this research. The analytical method used is descriptive analysis test, multiple regression analysis test, classic assumption test, partial test (t-test), and coefficient of determination test. The results of this study indicate that Cost Efficiency has no effect on disclosure of Islamic Social Reporting (ISR), Leverage has an effect on ISR disclosure, Institutional Ownership has no effect on ISR disclosure, and ProfitSharing Ratio has no effect on ISR disclosure.